PENGARUSUTAMAAN GENDER (PUG) DALAM TANTANGAN BUDAYA PATRIARKI - Henny Yusalia (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2014)
The term gender mainstreaming (PUG) refers to the understanding that the concept of gender should be encouraged to be understood by the public. Which emphasizes the aspect of gender equality and social justice role, must be maximized, so that domination and